Higher educational attainment is associated with longer telomeres in midlife: Evidence from sibling comparisons in the UK Biobank. (March 2022) - Amin, Vikesh; Fletcher, Jason M.; Sun, Zhongxuan; Lu, Qiongshi
Abstract: Prior studies have established that higher educational attainment is associated with a longer telomere length (TL), a marker of cellular aging. However, it is unclear whether extant associations are causal, since they are likely confounded by unobserved genetic, early-life and family background factors that are correlated with education and TL. We leverage sibling differences in TL, education and measured genetics (polygenic scores for educational attainment and TL) to estimate associations between educational attainment and TL in midlife for European ancestry individuals in the UK Biobank, while controlling for unobserved confounders shared by siblings. After controlling for genetics and shared background between siblings, we find suggestive evidence that high school graduates have longer telomeres than high school dropouts, but we find no differences in TL between high school dropouts and college graduates. Highlights: Estimate associations between education and telomere length (TL) in the UK Biobank. Control for confounding through sibling fixed-effects and polygenic scores. High school graduates have longer telomeres than high school dropouts.